Absolute lymphocyte count as predictor of overall survival for patients with multiple myeloma treated with single autologous stem cell transplant. Issue 9 (2nd September 2015) - Jimenez-Zepeda, Victor H.; Reece, Donna E.; Trudel, Suzanne; Chen, Christine; Franke, Norman; Winter, Andrew; Tiedemann, Rodger; Kukreti, Vishal
Abstract : Post-autologous stem cell transplant (ASCT) studies have demonstrated that absolute lymphocyte count (ALC) recovery is associated with prolonged survival in some hematological malignancies. To assess whether ALC recovery has prognostic significance in patients with multiple myeloma (MM) undergoing single ASCT, we conducted a retrospective analysis of ALC at different time-points in patients with MM. In total 769 consecutive patients who underwent single ASCT from January 2000 to December 2007 were evaluated. An ALC of ≥ 1400 cells/μL at day 0, day 15 and day 90 significantly correlated with a better overall survival (OS) (median OS of 111, 90.7 and 84 months vs. 74, 70.5 and 65 months, respectively, p < 0.001 for all time-points). Multivariate analysis showed that ALC is an independent prognostic factor for OS after ASCT. In conclusion, ALC is a surrogate marker of the host immune system that correlates with better survival in patients with MM undergoing single ASCT. Immunomodulatory drugs, vaccination strategies and cellular therapies in MM should be investigated.